Pemberian Makanan Tambahan pada Anak Bawah Dua Tahun (Baduta) di Desa Lawata Kabupaten Kolaka Utara - Grace Tedy Tulak; Iis Afrianty; Ekawati Saputri; Sahrul Poalahi Salu (Lembaga Pengembangan Kinerja Dosen, 2025)
Children under two years old (Baduta) are vulnerable to nutritional problems due to their rapid growth and development phase. Supplementary feeding (PMT) using locally sourced foods is an effort that can support adequate nutritional intake during this period. This community service activity aimed to increase mothers' knowledge regarding the importance of PMT and the introduction of nutritious local food ingredients that are easily accessible. The activity was conducted in Lawata Village, Kolaka Utara Regency, involving 30 mothers with Baduta. The method used was educational counseling and interactive discussion covering the definition, benefits, timing of supplementary feeding, and examples of local nutritious foods such as fish, eggs, tempeh, legumes, vegetables, and tubers. The results showed an improvement in participants' understanding of appropriate supplementary feeding practices. Mothers also expressed willingness to apply the knowledge gained in daily feeding practices at home. This program is expected to increase family awareness of balanced nutrition and encourage the use of local food sources to support optimal child growth and nutritional status improvement.